2022
DOI: 10.1039/d2ta00269h
|View full text |Cite
|
Sign up to set email alerts
|

Key to intimately coupling metal chalcogenides with a carbon nanonetwork for potassium-ion storage

Abstract: Intimately coupling metal chalcogenide (MC) with carbon material is critical for boosting their application performances. However, since the MCs and carbon materials are usually two types of incompatible materials, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In addition, the highresolution XPS spectrum of S 2p is shown in Figure 2d, the peaks of 161.2 eV and 162.3 eV can be assigned to the S 2p 3/2 and S 2p 1/2 of S 2À in SnS 2 and MoS 2 , respectively. [22,33,34,38,39] In addition, the shoulder peak at 164.5 eV can be attributed the CÀ SÀ C, suggesting the covalently bond of S with CNTs. [40][41][42] Thus, it can be concluded that the presence of MoS 2 and SnS 2 , which is consistent with the XRD and Raman results.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the highresolution XPS spectrum of S 2p is shown in Figure 2d, the peaks of 161.2 eV and 162.3 eV can be assigned to the S 2p 3/2 and S 2p 1/2 of S 2À in SnS 2 and MoS 2 , respectively. [22,33,34,38,39] In addition, the shoulder peak at 164.5 eV can be attributed the CÀ SÀ C, suggesting the covalently bond of S with CNTs. [40][41][42] Thus, it can be concluded that the presence of MoS 2 and SnS 2 , which is consistent with the XRD and Raman results.…”
Section: Resultsmentioning
confidence: 99%
“…The multidimensional structure can buffer the volume expansion, but the ion diffusion rate is limited by the long diffusion distance. 90,91 The hollow porous structure is better for improving the ion diffusion rate, and the spatial restriction is beneficial for regulating the in situ growth of ABXs. 92 The size of the nanoparticles is limited by the hollow structure, which alleviates the problems of particle aggregation and volume expansion and significantly enhances the stability of the structure.…”
Section: Control Of Morphology and Construction Of Nanocomposite Stru...mentioning
confidence: 99%
“…141,142 Simultaneously, the synergistic interaction between metals can buffer the volume change of ABXs and improve the electrochemical performance. 90 In bimetallic reaction systems, two metal ions were reduced almost simultaneously when their redox potentials were similar. The two metal atoms of the bimetal were uniformly mixed by metallic bonding to form an alloy or intermetallic compound.…”
Section: Alloysmentioning
confidence: 99%